Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025500
|View full text |Cite
|
Sign up to set email alerts
|

Subtle and Personal Workspace Requirements for Visual Search Tasks on Public Displays

Abstract: We explore how users approach and define personal space on large, public displays. Our results show that users of public displays use one of two strategies for visual search tasks: minimizers create a small window and work up close to the display, and maximizers expand content to its full resolution and work at a distance. We show that these interaction styles match predicted 'personal' and 'subtle' interaction zones, characterize typical width and height requirements for these interactions, and show that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…We also found that some publication lean on a previous definition, such as Vogel and Balakrishnan's concept of a "subtle interaction phase" [42,[77][78][79], but do not provide additional details on their own. Hence while these publications seemed relevant while skimming, they did not add to the subsequent analysis.…”
Section: Charting Subtle Interactionmentioning
confidence: 90%
See 1 more Smart Citation
“…We also found that some publication lean on a previous definition, such as Vogel and Balakrishnan's concept of a "subtle interaction phase" [42,[77][78][79], but do not provide additional details on their own. Hence while these publications seemed relevant while skimming, they did not add to the subsequent analysis.…”
Section: Charting Subtle Interactionmentioning
confidence: 90%
“…At the same time "[t]he information shown in this phase can be personal, but should be harmless, in that it should not be something that a user is highly protective of. " This notion of a subtle interaction zone was also applied by Wallace et al [79]. Similarly, Kukka et al studied two phases of interaction with a public display: "1) subtle interaction, where users can interact with the display through gestures or movement, and 2) direct interaction, when users interact with the display by directly manipulating it through e.g.…”
Section: Orthogonal Uses Of Subtletymentioning
confidence: 99%